146k views
3 votes
What is 2(n-1)+4n=2(3n-1)

User Rje
by
4.8k points

1 Answer

3 votes

Answer:

Infinite solutions

Explanation:

Distribute the 2 to (n - 1), and distribute the 2 to (3n - 1), like so:

2(n - 1) + 4n = 2(3n - 1)

2n - 2 + 4n = 6n - 2

Add like terms (2n and 4n):

6n - 2 = 6n - 2

Subtract 6n from both sides:

-2 = -2

Since we ended up with the same term on both sides, we can't do anything else, meaning this equation has infinite solutions.

User Christoph Dietze
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.